2020
DOI: 10.5802/crmath.50
|View full text |Cite
|
Sign up to set email alerts
|

Relative global dimensions and stable homotopy categories

Abstract: In this paper we study the finiteness of global Gorenstein AC-homological dimensions for rings, and answer the questions posed by Becerril, Mendoza, Pérez and Santiago. As an application, we show that any left (or right) coherent and left Gorenstein ring has a projective and injective stable homotopy category, which improves the known result by Beligiannis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The following undefined symbols can be referred in [2,5]. The latest related profound research conclusions on this subject can be found in [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The following undefined symbols can be referred in [2,5]. The latest related profound research conclusions on this subject can be found in [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%